Immunohistochemical Expression of MMP-9 in Subtypes of Ameloblastoma (Medical Forum Monthly, 2021)
Objective: To assess the immune expression of MMP-9 in ameloblastoma and its association with different histological subtypes of ameloblastoma.Study Design: Analytical / cross-sectional studyPlace and Duration of Study: This study was conducted at the Armed Forces Institute of Pathology, Rawalpindi (AFIP) from June 2016 till June 2017.Materials and Methods: In this study, total of 60 cases of ameloblastoma were included. Parafinembedded blocks of patients of both genders, diagnosed with ameloblastoma were included as experimental samples while necrotic, scarce and autolyzed cases were not included. The tumor was sub-classified histologically on the basis of WHO classified and section were stained with H&E followed by (IHC) staining for MMP-9.SPSS version 20 was used to analyse the final result analyzed using chi-square test.Results: Out of 60 cases of ameloblastoma, 32 were males and 28 were females. Mean age was 35.6 years with maximum 25 cases(83.3%) from mandible. On histopathological sub classification, 38 cases (63%) were diagnosed as follicular type, 14 cases(23.3%) were plexiform, 8 cases(13.3%) were acanthomatous type. All samples represent variable MMP-9 expression alongwith mild, moderate and strong intensity. Adjacent to the tumoral island invasive font was with highest reactivity. The strong immunoexpression, was seen in 75% acanthomatous and 57% plexiform, which was significantly different from follicular type with only 5.26%. Statistical test on MMP-9(P< 0.05) provide highest reactivity in acanthomatous typealongwiththe presence of substantial differences within histological variant.Conclusion: Our results proved the implication of MMP-9 in ameloblastoma growth and as a result their effectiveness in local aggressiveness monitoring in different subtypes of ameloblastoma.